RELIGIOUS TOLERANCE AND CULTURAL HARMONY IN ARAKAN PERAHU TRADITION - Syafii, Sufyan; Siti Yayu Magtufah (Balai Penelitian dan Pengembangan Agama Jakarta, 2024)
The Arakan Perahu tradition in Kalipasir Village, Tangerang, is a legacy from the ancestors commemorating the birthday of the Prophet Muhammad SAW, which has historical roots since the 4th Sultan of Banten in 1639. Over time, this tradition developed with the launch of ships as a symbol of the spread of Islam. Even though there was a hiatus during the political struggle (1955-1993), this tradition was carried out again with the name changed to “Safinatunnajah Wassalamah” in 1994. This tradition reflects tolerance between Muslims and ethnic Chinese in Kalipasir, with Muslims respecting the religious activities of ethnic Chinese. Interestingly, in 2023, the government will participate in the event because, in previous years, traditional activities were only carried out in Kalipasir Village. The government supported the activities of the Chinese with facilities and security, but there was an imbalance against the activities of the Muslims. Nevertheless, the Kalipasir people still maintain traditions as part of the Tangerang civilization, respect differences, and uphold the values of Pancasila.